Berani Hijau: Apakah Ada Masalah Literasi Lingkungan di Sekolah Dasar Negeri Pedesaan? - Fanny Sumirat; Wahyu Sopandi; Nana Supriatna; Udin Syaefudin Sa’ud (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to describe the actual condition of environmental literacy of public elementary schools students in rural areas. The research design uses a quantitative survey method. The research participants were 39 teachers in 15 public elementary schools in Sukabumi, West Java. The questionnaire used as an instrument to collect data. The results indicate that there are environmental literacy problems for public elementary schools students in rural areas. The results of this study found that there were factors causing low environmental literacy among students in public elementary schools in rural areas. Based on the data obtained, there are six causal factors regarding clean and healthy living, limited learning resources for students, lack of teacher approaches and strategies in introducing environmental education, low student concern for the environment, community involvement in protecting the environment, and the impact of natural disasters that occurred in the rural area.